Positional match running performance and performance profiles of elite female field hockey - Kapteijns, J. A.; Caen, K.; Lievens, M.; Bourgois, J. G.; Boone, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine if there is a link between the demands of competitive game activity and performance profiles of elite female field hockey players.